Inhalable Saharan dust induces oxidative stress, NLRP3 inflammasome activation, and inflammatory cytokine release. (February 2023) - Bredeck, Gerrit; Busch, Mathias; Rossi, Andrea; Stahlmecke, Burkhard; Fomba, Khanneh Wadinga; Herrmann, Hartmut; Schins, Roel P.F.
Graphical abstract: Highlights: Microbial components contribute to the pro-inflammatory potential of Saharan dust. Saharan dust induces oxidative stress and pro-inflammatory cytokine expression. Different in vitro persistence of Saharan dust versus silica-induced effects. Saharan dust activates the pro-inflammatory NLRP3 inflammasome pathway. Abstract: Desert dust is increasingly recognized as a major air pollutant affecting respiratory health. Since desert dust exposure cannot be regulated, the hazardousness of its components must be understood to enable health risk mitigation strategies. Saharan dust (SD) comprises about half of the global desert dust and contains quartz, a toxic mineral dust that is known to cause severe lung diseases via oxidative stress and activation of the NLRP3 inflammasome-interleukin-1β pathway. We aimed to assess the physicochemical and microbial characteristics of SD responsible for toxic effects. Also, we studied the oxidative and pro-inflammatory potential of SD in alveolar epithelial cells and the activation of the NLRP3 inflammasome in macrophage-like cells in comparison to quartz dusts and synthetic amorphous silica (SAS). Characterization revealed that SD contained Fe, Al, trace metals, sulfate, diatomaceous earth, and endotoxin and had the capacity to generate hydroxyl radicals. We exposed A549 lung epithelial cells and wild-type and NLRP3 -/- THP-1 macrophage-like cells to SD, three well-investigated quartz dusts, and SAS. SD induced oxidative stress in A549 cells after 24 h more potently than the quartz dusts. The quartz dusts and SAS upregulated interleukin 8 expression after 4 h and 24 h while SD only caused a transient upregulation. SD, the quartz dusts, and SAS induced interleukin-1β release from wild-type THP-1 cells>20-fold stronger than from NLRP3 -/- THP-1 cells. Interleukin-1β release was lower for SD, in which microbial components including endotoxin were heat-destructed. In conclusion, microbial components in SD are pivotal for its toxicity. In the epithelium, the effects of SD contrasted with crystalline and amorphous silica in terms of potency and persistence. In macrophages, the strong involvement of the NLRP3 inflammasome emphasizes the acute and chronic health risks associated with desert dust exposure.